Comparing the antireflux effect of laparoscopic proximal gastrectomy with double-flap technique reconstruction versus laparoscopic total gastrectomy with Roux-en-Y reconstruction for proximal early gastric cancer: study protocol for a multicentre, prospective, open-label, randomised controlled trial - Bin Yang; Lin Zhong; Yingying Zhu; Shengning Zhou; Yequan Xie; Jianan Tan; Guangyu Zhong; Fanghai Han (BMJ Open)
Introduction Laparoscopic proximal gastrectomy with double flap technique (LPG-DFT) reconstruction has been used for proximal early gastric cancer in recent years. However, its feasibility and safety remain uncertain, as only a few retrospective studies have contained postoperative complications and long-term survival data. LPG-DFT for proximal early gastric cancer is still in the early stages of research. Large-scale, prospective randomised controlled trials (RCTs) are necessary to assess the value of LPG-DFT for proximal early gastric cancer.Methods and analysis This study is a multicentre, prospective, open-label, RCT that investigates the antireflux effect of LPG-DFT compared with laparoscopic total gastrectomy with Roux-en-Y (LTG-RY) reconstruction for proximal early gastric cancer. A total of 216 eligible patients will be randomly assigned to the LPG-DFT group or the LTG-RY group at a 1:1 ratio using a central, dynamic and stratified block randomisation method, if inclusion criteria are met. General and clinical data will be collected when the patient is enrolled in the study and keep pace with the patient at each stage of his medical and follow-up pathway. The primary endpoint is the proportion of patients with reflux esophagitis (Los Angeles Grade B or more) within 12 months postoperatively. The secondary endpoints included intraoperative outcomes, postoperative recovery, postoperative pain assessment, pathological outcomes, postoperative quality of life, postoperative nutrition status, morbidity and mortality rate, and oncological outcomes (3-year overall survival (OS), 3-year disease-free survival (DFS), 5-year DFS and 5-year OS).Ethics and dissemination The protocol is approved by the Sun Yat-Sen Memorial Hospital of Sun Yat-Sen University ethics committee (registration number: SYSKY-2022-276-02) on 28 September 2022.We will report the positive as well as negative findings in international peer-reviewed journals.Trial registration number NCT05890339.